Urban ecology: An introduction - James, Philip; Douglas, Ian (London Routledge, 2024)
This fully revised second edition reflects the great expansion in urban ecology research, action, and teaching since 2015. Urban ecology provides an understanding of urban ecosystems and uses nature-based techniques to enhance habitats and alleviate poor environmental conditions.
Keywords: Urban ecology; City planning; Sustainable development